ACCURACY AND SAFETY OF CT-GUIDED STEREOTACTIC SURGERY IN THE DIAGNOSIS OF DEEP SEATED, SMALL AND ELOQUENT AREA BRAIN LESIONS - Najm us Saqib; Lal Rehman et al. (Journal of University Medical & Dental College, 1970)
ABSTRACT Objective: To assess the accuracy of the target trajectories and complications risk rate of computed tomography (CT) guided stereotactic surgery in the diagnosis of deep seated, small and eloquent area brain lesion. Methods: This three years study from March 2006 to April 2009 was conducted at Department of Neurosurgery, Jinnah Postgraduate Medical Centre Karachi. The study includes 44 patients with clinical and radiologicaly diagnosed brain space occupied lesion (SOL). Relevant history was obtained and clinical and neurological examination was done. CT scan brain and magnetic resonance imaging (MRI) brain with contrast performed. The Cosman Roberts Well (CRW) arc based frame used for all procedures. Results: Procedure was carried on 44 patients, 15 females and 29 males with female to male ratio of 1:1.93. Biopsy was performed for deep seated lesions n=23, midline and corpus callosum tumors n=11, lobar lesion n=9 and in 1 patient biopsy taken for suprasellar cystic SOL, with reservoir placement. Astrocytic neoplasm was the commonest which include n=26 (59.09%) cases. Forty two biopsies were positive and clinically and radiologicaly correlated. Two biopsies results were not confirmed. The mortality were n=2 (4.45%). Conclusion: Stereotactic procedure is easy to perform, accurate in targeting the lesion, and spare patients from undergoing major surgical procedures. The specimen taken for biopsy is adequate for diagnosis. Target localization is more than 95% if meticulous methodology is applied. Overall, complications arising from stereotactic brain biopsy are infrequent but can be disastrous.